Controlling antifungal activity with light: Optical regulation of fungal ergosterol biosynthetic pathway with photo-responsive CYP51 inhibitors - Zhuang Li; Na Liu; Wanzhen Yang; Jie Tu; Yahui Huang; Wei Wang; Chunquan Sheng (Elsevier, 2023)
Invasive fungal infections (IFIs) have been associated with high mortality, highlighting the urgent need for developing novel antifungal strategies. Herein the first light-responsive antifungal agents were designed by optical control of fungal ergosterol biosynthesis pathway with photocaged triazole lanosterol 14α-demethylase (CYP51) inhibitors. The photocaged triazoles completely shielded the CYP51 inhibition. The content of ergosterol in fungi before photoactivation and after photoactivation was 4.4% and 83.7%, respectively. Importantly, the shielded antifungal activity (MIC80 ≥ 64 μg/mL) could be efficiently recovered (MIC80 = 0.5-8 μg/mL) by light irradiation. The new chemical tools enable optical control of fungal growth arrest, morphological conversion and biofilm formation. The ability for high-precision antifungal treatment was validated by in vivo models. The light-activated compound A1 was comparable to fluconazole in prolonging survival in Galleria mellonella larvae with a median survival of 14 days and reducing fungal burden in the mouse skin infection model. Overall, this study paves the way for precise regulation of antifungal therapy with improved efficacy and safety.